Dispersion of the surface magnetoplasmons - Ivko, S.V.; Denysenko, I.B.; Smolyakov, A.I.; Azarenkov, N.A. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
We study the dispersion properties and transmission of a p-polarized electro-magnetic wave in a two-layer plasma structure in presence of an external magnetic field. The conditions for resonance transmission are found. The anomalous transparency is attributed to excitation of surface waves at plasma-plasma interface. The dispersion relation for the surface mode at plasma-plasma interface in magnetic field is studied and compared with that for a plasma-vacuum system.